2020
DOI: 10.3390/ijerph17155413
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Indoor Pollutants Exposure on Allergy and Lung Inflammation: An Activation State of Neutrophils and Eosinophils in Sputum

Abstract: Background: To explore the inflammation phenotypes following indoor pollutants exposure based on marker expression on eosinophils and neutrophils with the application of chemometric analysis approaches. Methods: A cross-sectional study was undertaken among secondary school students in eight suburban and urban schools in the district of Hulu Langat, Selangor, Malaysia. The survey was completed by 96 students at the age of 14 by using the International Study of Asthma and Allergies in Children (ISAAC) and Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…Three groups of kids with varying levels of PM2. 35 By increasing the pulmonary polymorphonuclear leukocyte (PMN)/white blood cell ratio and the PMN count in human peripheral blood, which was both mediated by VCAM-1, high PM2.5 exposure (>75 μg/m 3 ) was found to be able to cause inflammation and lung damage. This study involved 32,704 participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three groups of kids with varying levels of PM2. 35 By increasing the pulmonary polymorphonuclear leukocyte (PMN)/white blood cell ratio and the PMN count in human peripheral blood, which was both mediated by VCAM-1, high PM2.5 exposure (>75 μg/m 3 ) was found to be able to cause inflammation and lung damage. This study involved 32,704 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Khairul Nizam Mohd et aI. 's 35 study showed that exposure to PM2.5 can trigger inflammatory response mechanisms by causing eosinophils to granulate. 37 This finding also suggested that the primary alteration during exposure to ambient PM2.5 in the real world may be neutrophil inflammation brought on by infection and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in Selangor (Malaysia) focused on assessing the allergy and lung inflammation promoted by exposure to different indoor pollutants (PM 2.5 , PM 10 , NO 2 and CO 2 ) in scholar environments, based on marker expression on eosinophils and neutrophils [ 14 ]. A total of 96 students from eight suburban and urban schools answered to standardized questionnaires and their fractional exhaled nitric oxide (FeNO) was evaluated, along with allergic skin prick test and sputum induction (which was later analysed for the expression of CD11b, CD35, CD63 and CD66b on eosinophils and neutrophils).…”
Section: Health Impacts Of Human Exposure To Air Pollutionmentioning
confidence: 99%
“…Inflammation is a part of body’s defense in response to injury or infection, but chronic inflammation, which can result from exposure to environmental chemicals, plays a key role in many disorders, such as autoimmune diseases and asthma [ 23 – 25 ]. Eosinophils and neutrophils are two types of white blood cells that are activated to fight diseases, infections, and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils and neutrophils are two types of white blood cells that are activated to fight diseases, infections, and inflammation. Eosinophilia and neutrophilia are conditions in which the number of eosinophils or neutrophils, respectively, increases above the normal levels in affected tissue [ 23 , 26 ]. Under these conditions, neutrophil myeloperoxidase and eosinophil peroxidase overproduce halogenated species such as HOCl or HOBr that react with tyrosine, increasing chlorotyrosine (CY) [ 27 , 28 ] and bromotyrosine (BY) [ 28 ] levels, which are recognized as inflammatory biomarkers (IBs) [ 17 , 28 ].…”
Section: Introductionmentioning
confidence: 99%